Role of cervical cancer screening during prenatal checkups for infectious diseases: A retrospective, descriptive study. Issue 5 (May 2022) - Maruyama, Yasuyo; Sukegawa, Akiko; Yoshida, Hiromi; Iwaizumi, Yukiha; Nakagawa, Sayako; Kino, Tamina; Suzuki, Yukio; Kubota, Kazumi; Hirabuki, Tomoo; Mizushima, Taichi; Miyagi, Etsuko
Objective: This study was conducted to evaluate the status and role of cervical cytology affected by human papillomavirus infection and other infectious diseases screened during routine prenatal checkups. Methods: We retrospectively examined medical records containing the screening results for infectious diseases and cervical cancer in women who delivered neonates in our hospital from 2014 to 2017. Results: Among 3393 deliveries, 18.8% of women underwent a regular cervical cancer screening within 1 year of becoming pregnant, and 2641 women underwent a cervical cytology screening during this pregnancy. The cytological diagnostic results showed that 2562 women (97.0%) were negative for intraepithelial lesions or malignancy, whereas 79 (3.0%) had abnormal results. Of those with abnormal cytology results, 70 had abnormal cytology that was newly detected in this pregnancy, and 42 had grade ≥1 cervical intraepithelial neoplasia lesions. Spatulas were the most frequently used cytological sampling instruments, followed by cotton swabs. Cervical cytology revealed no major adverse reactions during these pregnancies. Conclusions: Our results confirm the importance of screening for infectious diseases during pregnancy. Only 20% of the women underwent a regular pre-pregnancy cervical cytology screening. Cervical cytology screening during pregnancy may currently be playing a crucial role in preventing cervical cancer in Japan.